Comparison of the effects of transdermal and oral rivastigmine on cognitive function and EEG markers in patients with Alzheimer’s disease - Moretti, Davide V.; Frisoni, Giovanni B.; Binetti, Giuliano; Zanetti, Orazio (Frontiers in Aging Neuroscience, 2014)
Background: Alzheimer's disease (AD) is the most common cause of dementia in older patients. Rivastigmine (RV, Exelon®, Novartis), a reversible cholinesterase inhibitor, improves clinical manifestations of AD and may enhance ACh-modulated electroencephalogram (EEG) alpha frequency. This pilot study aimed to determine the effects of two formulations of RV (transdermal patch [TV-RDP] and oral capsules [TV-CP]) on alpha frequency, in particular the posterior dominant rhythm, and cognitive function (assessed by the Mini-Mental State Examination [MMSE]) in patients with AD. Methods: Subjects with AD were assigned to receive either RV-TDP 10 cm2 or RV-CP 12 mg/day. All patients underwent EEG recordings at the beginning and end of the 18-month study period using P3, P4, O1 and O2 electrodes, each at high (10.5–13.0 Hz) and low (8.0–10.5 Hz) frequency. MMSE scores were determined at the start of the study (T0) and at three successive 6-month intervals (T1, T2 and T3). Results: RV-TDP administration (n=10) maintained cognitive function as evidenced by stable MMSE scores from baseline to 18 months (21.07 ± 2.4 to 21.2 ± 3.1) compared with a decrease in MMSE score with RV-CP (n=10) over 18 months (18.3 ± 3.6 to 13.6 ± 5.06 [adjusted for covariates p=0.006]). MMSE scores were significantly different between treatment groups from 6 months (p=0.04). RV-TDP also increased the spectral power of alpha waves in the posterior region measured with electrode P3 in a significantly great percentage of patients than TV-CP from baseline to 18 months; 80% versus 30%, respectively (p=0.025 [χ2 test]). Conclusion: RV-TDP was associated with a greater proportion of patients with increased posterior region alpha wave spectral power and significantly higher cognitive function at 18 months, compared with RV-CP treatment. Our findings suggest that RV-TDP provides an effective long-term management option in patients with AD compared with oral RV-CP. This study is a pilot, open-label study with a